Immatures of Palaearctic species of the weevil genus Tychius (Coleoptera, Curculionidae): new descriptions and new bionomic data with an evaluation of their value in a phylogenetic reconstruction of the genus - Skuhrovec, Jiří; Gosik, Rafał; Caldara, Roberto (Zootaxa, 2014)
Larvae of 14 species and pupae of 12 species of Palaearctic Tychius Germar, 1817 are described for the first time. Larvae and pupae of T.meliloti Stephens, 1831, T. squamulatus Gyllenhal, 1835 and T. quinquepunctatus (Linnaeus, 1758), are redescribed with addition of new characters. They belong to 10 of 22 groups of species assembled through adult morphological characters in this region and, like all other Tychius with known biology, the studied species live on Leguminosae Papilionoideae, belonging to the tribes Genisteae, Loteae, Galegeae, Trifolieae and Vicieae. Generally larvae, but not pupae, show a few characters useful to support some groupings previously postulated on adult morphology, and also suggest some phylogenetic relationships among groups although these are partly weak because of several clear parallelisms or convergences. One of the most numerous and better known group of species, the T. stephensi group living on Trifolieae, is supported by two distinctive larval character states, whereas all the other groups seem to be distinguishable from each other at least by a unique larval character state. New bionomic data concerning larval and pupal development and adult emergence are reported for all the described species. These data confirm that this genus is highly homogeneous in habits and times of development, with unique adaptive differences in adult emergence and overwintering according to the single or double seasonal flowering of the host plant. On the basis of morphological characters of immatures and adults, a possible concordance between the evolution of Tychius and that of their host plants is discussed.